Influence of carrier effect on Pd/Al2O3 for methane complete catalytic oxidation - Peng, Shengpan; Ma, Ziran; Ma, Jing; Wang, Hongyan; Chen, Jingyun; Wei, Hui; Li, Yonglong; Ao, Zhimin; Wang, Baodong (Frontiers in Chemistry, 2022)
Pd/Al2O3 catalysts modified by different chemical elements (Mg, Si, Ce, and Zr) were tested for methane (CH4) catalytic combustion, and PdO nanoparticles loaded on modified Al2O3 were systematically studied. These conditions assess the carrier effects of Pd/Al2O3 and acid strength influences on CH4 combustion. We observed carrier effects on activation energy through tuning Pd 3d binding energies (BEs) and on pre-exponential factors (A) through Pd dispersion and acidity on supports. When the BE of Pd 3d5/2 is 337.3 eV, PdO nanoparticles loaded on modified Al2O3 have excellent activity in cracking the C−H bond of CH4, which leads to the lowest activation energy (Ea), regardless of the size effect of the PdO nanoparticle. Furthermore, a theoretical construction that acid sites on catalysts promote the reversible elementary step (2Pd−OH ↔ Pd−O* + Pd* + H2O) right shifts improving the A dependency on the quantity of exposed Pd* and Pd−O*. As a result, Al2O3, as the carrier, not only modifies the electronic characteristics and size of supported PdO nanoparticles but also participates in the reaction process via acid sites on the surface of Al2O3.